How the East Was Won: Supply Chain Restructuring in the Eastern European Beer Market; Wie der Osten gewonnen wurde: Restrukturierung der Versorgungskette im osteuropaïschen Biermarkt - Kristine Van Herck; Johan F.M. Swinnen; Koen Deconinck (German Journal of Agricultural Economics (GJAE), 2012)
Like all markets in the former communist countries, the Eastern European beer market has been strongly affected by the economic reforms in the beginning of the 1990s. In the first years after reforms, there was a substantial decline in the production of barley, malt and beer. However, the brewery sector soon attracted interest from foreign investors, who faced problems in sourcing sufficient high quality malt in order to produce high quality beer. Therefore, they reintroduced vertical coordination in the supply chain to obtain malt and barley that consistently met their quality requirements. The associated change in beer quality has been one of the drivers behind the spectacular growth of beer consumption in several Eastern European countries. Most remarkable was the growth in the Russian beer market, where beer consumption more than quadrupled over the course of a decade. In this paper, we describe and analyze the dramatic restructuring of the beer industry and the changes in the industrial organization of its supply chain over the past two decades. In addition, we document how the drastic improvement in the quality of beer has been an important driver behind rapid growth in beer consumption in Russia.
Keywords: 330; Bier; Markt; Systemtransformation; Produktqualität; Konsumentenverhalten; Osteuropa